Developing the leadership competencies of department heads in Saudi universities in light of the human capacity development program - Garrah, Ali Yahya (Journal of Educational and Psychological Sciences, 2024)
This study aimed to identify the degree of availability of leadership competencies among department heads in Saudi universities in light of the human capacity development program, reveal the challenges they face, and present proposals for developing their leadership competencies. To achieve these goals, a descriptive survey method was used, a questionnaire was used as a tool for collecting data, and the study was applied to department heads in all colleges at King Saud University. The results of the study reached the following: The degree of availability of leadership competencies was moderate, with the general arithmetic mean reaching (3.43), with a moderate degree of agreement with the overall direction of the axis. The phrase: (planning) came in first place with a moderate degree of agreement, an arithmetic mean of (4.10), The degree of challenges was high, as the overall average for the axis was (3.83), which confirms the existence of challenges facing department heads in Saudi universities to develop leadership competencies in light of the human capacity development programme. The phrase came: (Administrative burdens) ranked first with a mean of (4.47), and a very high degree of agreement, The score for development proposals was highly agreeable, with the overall average for the axis reaching (3.72), and the statement that states: (holding directed training programs) came in first place. The study reached a number of recommendations, the most prominent of which are: holding intensive training programs for department heads directed at developing their leadership competencies, providing sufficient administrative staff to assign them to accomplish some non-technical administrative tasks, and providing sufficient financial support to develop the leadership competencies of department heads.
Keywords: Leadership competencies; Heads of Departments; Human capabilities development program